comparison of sinusoidal‚ square wave‚ sawtooth‚ and staircase forms of transient ramped voltammetry when a reversible process is analysed in the frequency domain - Gavaghan, D; Elton, D; Bond, A (2001)
Sawtooth and squarewave forms of transient voltammetry have been simulated in order that a detailed comparison with results previously undertaken on sinusoidal and square wave forms of voltammetry could be made in the frequency domain. All theoretical calculations were performed for a reversible process, assuming a linear de ramped potential is present, and using numerical simulations which were analysed using the fast Fourier transform method. On the basis of this study, the conclusion is reached that transient voltammetric methods, where a periodic signal is superimposed onto a de potential, are part of a family of techniques having essentially c